Efficient release from promoter-proximal stall sites requires transcript cleavage factor TFIIS. - Adelman, K.; Marr, M.T.; Werner, J.; Saunders, A.; Ni, Z.; Andrulis, E.D.; Lis, J.T. (Molecular Cell, 2005)
Uninduced heat shock genes are poised for rapid activation, with RNA polymerase II (Pol II) transcriptionally engaged, but paused or stalled, within the promoter-proximal region. Upon heat shock, this Pol II is promptly released from the promoter region and additional Pol II and transcription factors are robustly recruited to the gene. Regulation of the heat shock response relies upon factors that modify the efficiency of elongation through the initially transcribed sequence. Here, we report that Pol II is susceptible to transcription arrest within the promoter-proximal region of Drosophila hsp70 and that transcript cleavage factor TFIIS is essential for rapid induction of hsp70 RNA. Moreover, using a tandem RNAi-ChIP assay, we discovered that TFIIS is not required to establish the stalled Pol II, but that TFIIS is critical for efficient release of Pol II from the hsp70 promoter region and the subsequent recruitment of additional Pol II upon heat induction.